Non-Sterilized Fermentation of 2,3-Butanediol with Seawater by Metabolic Engineered Fast-Growing Vibrio natriegens - Meng, Wensi; Zhang, Yongjia; Ma, Liting; Lü, Chuanjuan; Xu, Ping; Ma, Cuiqing; Gao, Chao (Frontiers in Bioengineering and Biotechnology, 2022)
Sustainable and environment-friendly microbial fermentation processes have been developed to produce numerous chemicals. However, the high energy input required for sterilization and substantial fresh water consumption restrict the economic feasibility of traditional fermentation processes. To address these problems, Vibrio natriegens, a promising microbial chassis with low nutritional requirements, high salt tolerance and rapid growth rate can be selected as the host for chemical production. In this study, V. natriegens was metabolic engineered to produce 2,3-butanediol (2,3-BD), an important platform chemical, through non-sterilized fermentation with seawater-based minimal medium after expressing a 2,3-BD synthesis cluster and deleting two byproduct encoding genes. Under optimized fermentative conditions, 41.27 g/L 2,3-BD was produced with a productivity of 3.44 g/L/h and a yield of 0.39 g/g glucose by recombinant strain V. natriegensΔfrdAΔldhA-pETRABC. This study confirmed the feasibility of non-sterilized fermentation using seawater to replace freshwater and other valuable chemicals may also be produced through metabolic engineering of the emerging synthetic biology chassis V. natriegens.